SYNERGISTIC EFFECT BETWEEN THIOL COLLECTORS IN REACTION WITH SULPHIDE MINERALS - Riaz, M; Khan, A R; Khan, Mumiaz; Khan, Kamin; Jan, Asadullah (Biological Sciences - PJSIR, 2001)
The study of synergism between potassium ethyl xanthate (Ketx) and sodium diethyl dithiocarbamate (Dtc) in reaction with heazlewoodite (Ni3S2) is described. It has been demonstrated that its occurrence can be explored by simple cyclic voitametry and adsorption measurements. Correlation was obtained between flotation recoveries, adsorption isotherms and cyclic voitametry measurements. The maximum synergistic effect between Ketx and Dtc was observed at the ratio of 0.35:0.65.